Level of Acceptance and Use Measurement of Electronic Money Technology Using UTAUT Model - Frans Sudirjo; Asri Ady Bakri; Andy Ismail; Putri Ekaresty Haes; Sarwo Hakim (SEULANGA SYSTEM PUBLISHER, 2023)
By increasing transaction speed and decreasing transaction costs, electronic payment innovations make cashless payment systems more effective. Electronic money is used in a variety of transactions, such as paying for commuter line tickets, paying for Trans Jakarta tickets, paying tolls, and shopping at supermarkets. However, in practice, it shows that users' understanding and awareness of electronic money are still not optimal, and there are problems with electronic money reader sensors. Therefore, it is crucial to undertake research on the acceptance and use of electronic money because this is one of the key elements in the system's successful deployment. In order to ascertain the current state of user acceptance and usage of electronic money, this study used the PLS-SEM analytic technique to look at the factors from the UTAUT 2 model that have an impact on user acceptability of electronic money. According to the findings, users who utilize electronic money have behavioral intentions and use behaviors that are 88% and 26%, respectively. Then, of the 12 hypotheses put out, Social Influence on Behavioral Intention and Facilitating Conditions on Behavioral Intention were the two that were rejected. Despite the fact that 60% of new users continue to use electronic money after one to two years, not enough nominal is utilized in a single week, according to the results of using it.